Forward-Looking Sustainability Agency for Developing Future Cruise Ships - Jokinen, Leena; Palonen, Tuire; Kalliomäki, Helka; Apostol, Oana; Heikkilä, Katariina (MDPI, 2020)
The study addressed sharing of futures insights as a component of sustainability agency for long-term company enhancement in an interorganizational shipbuilders’ network. The purpose was to analyze social structures under “agency” terminology. This joint sustainability project involved a partnership of firms, academia, and nongovernmental organization (NGO) actors in collaborative cruise ship building. The study adapted a mixed method approach where social network analysis (SNA) was enriched with other contextual data to make network data more applicable and accessible. The results revealed a loose and thin network structure, with relatively high trust among network actors. The network’s social structure was found to facilitate insight sharing. Lead firm actors clearly played a central role in enhancing sustainability, and the researchers, as well as industrial association actors, made a significant contribution to insight sharing and transmission. The findings suggest that the case network would benefit from an open and balanced social structure that incorporates a number of insight brokers to enhance forward-looking sustainability agency (F-L SA). Futures insight sharing enhances agency in the context of joint sustainability actions and improves capacity to respond to systemic challenges. Understanding how proactive agency can be promoted in network settings strengthens strategic aspects of managerial practice and contributes to discourse around sustainability agency.
Keywords: sustainability agency; future; forward-looking; cruise ship building; social network analysis; fi=Aluetiede|en=Regional Studies|